Making a living in war times. Wages in Tucuman in the first half of the 19th Century (Quinto Sol, 2019)
In a political and economic context so troubled and chaotic as the first decades of the 19th century, obtaining resources for subsistence was without doubt, one of the main challenges for most of the population in Tucumán. The shortage of money, the erratic behavior of prices, the demands of the war, and the conflictive building of the provincial State, among other factors, created a situation of instability and uncertainty that impacted on the level and evolution of wages. In this context, the local historiography ventured into the behavior of the salaries of public employees, from a vast salary scale spanning different social urban sectors of the nineteenth-century. This article expands the spectrum of analysis including skilled and unskilled private-sector workers.
Keywords: wages; job; subsistence